STUDI MEDIA SOSIAL FACEBOOK SEBAGAI SALURAN MEDIA GROUP PEMBELAJARAN ELEKTRONIKA DAN INDUSTRI SISWA SMK NEGERI 1 CIMAHI - Saeful Anwar, - (2012)
Utilization of communication media of the Internet can be accessed all people, good parents, adolescent, and children. Through the internet people communicate with each other, utilizing the virtual world of social networking media like facebook. Learning through "Facebook as a Social Media Study Media Group Learning Channel and Industrial Electronics Students SMK Negeri 1 Cimahi" aims to describe the role of networking facebook, advantages and disadvantages, as well as the responses of students and teachers about the role of networking facebook via online portfolio. The results showed that in general the role of networking in a facebook online portfolio goes well. It is shown through research findings, including the form of assessment is considered by students and teachers exciting and fun, generate pride in themselves as students or of his best work on display (62.5%), increase motivation and increase students' learning experience (87.5 %), stimulate the enthusiasm of students create reports work better (75%), and the time used does not interfere with the learning process. However, it still found problems, including delays in the delivery report students' work because of technical problems such as disruption of internet networks, as well as students in accessing kekurangaktifan facebook account (12.5%). Students admitted through the facebook administration tasks can increase motivation and stimulate students in making a better job reporting the results, with learning facebook can be used as an alternative medium of learning groups Electronics Industry and assessing student work.